Network Efficiency and Posterior Alpha Patterns Are Markers of Recovery from General Anesthesia: A High-Density Electroencephalography Study in Healthy Volunteers - Blain-Moraes, Stefanie; Tarnal, Vijay; Vanini, Giancarlo; Bel-Behar, Tarik; Janke, Ellen; Picton, Paul; Golmirzaie, Goodarz; Palanca, Ben J. A.; Avidan, Michael S.; Kelz, Max B.; Mashour, George A. (Frontiers in Human Neuroscience, 2017)
Recent studies have investigated local oscillations, long-range connectivity, and global network patterns to identify neural changes associated with anesthetic-induced unconsciousness. These studies typically employ anesthetic protocols that either just cross the threshold of unconsciousness, or induce deep unconsciousness for a brief period of time—neither of which models general anesthesia for major surgery. To study neural patterns of unconsciousness and recovery in a clinically-relevant context, we used a realistic anesthetic regimen to induce and maintain unconsciousness in 8 healthy participants for three hours. High-density electroencephalogram (EEG) was acquired throughout and for another three hours after emergence. Seven epochs of 5-minute eyes-closed resting states were extracted from the data at baseline as well as 30, 60, 90, 120, 150 and 180 minutes post-emergence. Additionally, 5-minute epochs were extracted during induction, unconsciousness and immediately prior to recovery of consciousness, for a total of 10 analysis epochs. The EEG data in each epoch were analyzed using source-localized spectral analysis, phase-lag index, and graph theoretical techniques. Posterior alpha power was significantly depressed during unconsciousness, and gradually approached baseline levels over the three-hour recovery period. Phase-lag index did not distinguish between states of consciousness or stages of recovery. Network efficiency was significantly depressed and network clustering coefficient was significantly increased during unconsciousness; these graph theoretical measures returned to baseline during the three-hour recovery period. Posterior alpha power may be a potential biomarker for normal recovery of functional brain networks after general anesthesia.